A Longitudinal Study of How Highlighting Web Content Change Affects People's Web Interactions - Teevan, Jaime; Dumais, Susan; Liebling, Dan (Proc. 2010 ACM Conf. on Human Factors in Computing Systems (CHI 2010), 2010)
The Web is constantly changing, but most tools used to access Web content deal only with what can be captured at a single instance in time. As a result, Web users may not have a good understanding of the changes that occur. In this paper we show that making Web content change explicitly visible allows people to interact with the Web in new ways. We present a longitudinal study in which 30 people used a Web browser plug-in that caches visited pages and highlights text changes to those pages when revisited. We used a survey to capture their understanding of Web page change and their own revisitation patterns at the beginning of use and after one month. For a majority of the participants, we also logged their Web page visits and associated content change. Exposing change is more valuable to our participants than initially expected, making them aware of how dynamic content they visit is and changing their interactions with it.